Implementasi Algoritma Naïve Bayes Classifier Dalam Penerimaan Karyawan - Edward Robinson Siagian; Doansi Tarihoran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The final research report of this study aims to find out how the employee recruitment procedure at PT. Kreasibeton Nusapada, because human resources are a component that has a very important role in a company. In today's technological age, some companies have used certain methods in making choices to recruit new employees. This is because the assessment used to obtain competent new employees should be an objective assessment. In this research, an assessment method will be developed to make it easier for the HRD (Human Resource Department) to select competent candidates to fill certain positions needed by the company. The assessment will be calculated by assessing all the criteria that must be met by prospective company employees, where the assessment is made with standards predetermined by management. The research produced a suitable candidate to fill the position of HSE (Health Safety Environment) staff at PT Kreasibeton Nusapersada, namely Rizki Vadlin with a final score of 1.75 which was calculated based on the Naïve Bayesian Classifier Algorithm. The results of this study indicate that the process of assessing the competence of prospective employees to fill available positions in the company is proven to produce an objective and effective assessment in accordance with the criteria set by the company's managemen.